AL-RADA’AH DALAM KONTEKS KEKINIAN - Andi Herawati; Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
Al-Rada'ah in terms of Islamic law has a very important position, because it has an impact on whether or not a man marries a woman. If a man as a child breastfeeds a woman who is not a mother or a woman who is unlawful for him to marry, it is forbidden for him to marry the mother where he is breastfeeding, as well as all women who have nasab with the nursing mother, both vertically and horizontally. . The views of scholars on determining the mahram of marriage because al-rada'ah (breastfeeding) is strict, some are very careful and some are easy. Imam Shafi'i and some of Imam Ahmad's students require marriage to be mahram if breast milk has entered the baby's abdominal cavity, either directly from the mother's nipple or not, pure or mixed, a lot or a little as long as the breast milk substance has not disappeared. The Hanafiyah and Abu Thaur groups require that the marriage of mahram to pure breast milk or at least contain more elements of breast milk than the mixture. Meanwhile, Ibn Hazm from the Zahiri school limits the mahram of marriage in the category of al-rada'ah meaning, namely breastfeeding by sucking the nipple of the breastfeeding mother with her mouth, which is not included in the category of meaning al-rada'ah does not forbid marriage.